Chtoby nash gandbol vsegda byl vperedi - Lubyshev, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
After a 10-years-break the Russian national team last year became again World champion in women's handball. Interview with the former manyfold Russian champion and European Cup holder and now Doctor of Science Valentina Ignateva.